Standardization and digital enclosure the privatization of standards, knowledge, and policy in the age of global information technology - Schoechle, Timothy D. (Advances in IT standards and standardization research series., 2009)
"This study of the privatization of standards and standardization seeks to establish a framework of analysis for public policy discussion and debate with such related issues as technical innovation, access to information and media, intellectual property, and emerging industrial economic development"--Provided by publisher.